ANALISIS BUTIR SOAL PILIHAN GANDA PENILAIAN TENGAH SEMESTER PADA PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR NEGERI 39 PONTIANAK KOTA - Widayanti, Weni; Bistari, Bistari; Suparjan, Suparjan (universitas hamzanwadi, 2021)
This study aims to analyze the multiple-choice questions for Mid-Semester Assessment in the thematic learning of class V at 39 Pontianak City Elementary Schools based on validity, level of difficulty, discriminatory power, effectiveness of distractors, and reliability. This research is a descriptive quantitative method. The Mid-Semester Assessment Question consists of 2 themes, namely theme 6 (20 points) and theme 7 (19 points). The questions were analyzed based on validity, level of difficulty, discriminatory power, effectiveness of distractors and reliability using Microsoft Excel 2010. The subjects in this study were students of class V. The data collection technique was carried out with documentation techniques. The results of this study indicate that the questions are of good quality. (1) The validity of the theme 6 questions as many as 19 items (95%), theme 7 as many as 18 items (94.74%) is said to be valid. (2) The level of difficulty in theme 6 is 13 items (68.42%) in the easy category, and 2 items (10.53%) in the difficult category, in theme 7 there are 11 items (61.11%) in the easy category, so it includes questions that not of good quality in terms of difficulty level. (3) The distinguishing power of theme 6 is 10 items (52.63%) in the bad category and 1 item (5.26%) in the good category, theme 7 is 6 items (33.33%) in the bad category and 3 items (16.67%) good category so that the questions are of moderate quality in terms of distinguishing power. (4) The effectiveness of distractors for theme 6 is 1 item (5.26%) in very good category, 8 items (42.11%)in good category, 6 items (31.58%) in poor category, theme 7 is 4 items (22 ,22%) in very good category, 4 items (22.22%) in good category, 3 items (16.67%) in poor category, so that the questions are of good quality in terms of distractor effectiveness. (5) The reliability of theme 6 questions is 0.9592, theme 7 is 0.8950 so that the questions are of good quality because of high reliability.